BUSINESS PERFORMANCE OF AGGREGATOR BUSINESS IN AGRICULTURE DURING COVID-19 PANDEMIC - Janita Sembiring Meliala; Siti Jahroh (Journal of Islamic, Social, Economics and Development, 2022)
Advances in information technology (IT) have also driven a change from traditionalapproaches to new approaches in agriculture or in other words the revolution in the fourthagricultural sector (Agriculture 4.0). IT has triggered the emergence of aggregator business inagriculture. With the Covid-19 outbreak, movement restrictions were made so that the majorityof buying and selling was carried out online. The existence of restricted movement due to theCovid-19 pandemic has decreased farmers' income due to difficulties in selling their products,while consumers who usually shop at the market switched to online shopping. The intermediary,in this case the aggregator that connects farmers directly with consumers online, will be ofgreat help to both parties. Thus, this study aims to (1) analyze the business processes of theaggregator business during Covid-19 and (2) analyze the business performance of theaggregator business during Covid-19 compared to before. The questionnaire survey throughgoogle form was distributed to aggregator business players in September 2020. The data wereanalyzed by descriptive statistics through tabulation. Based on our findings, there are twoimportant points. Firstly, through the advance of information technology, the aggregators wereable to connect the agribusiness system, i.e., farmers in on-farm, inputs supplier in up-stream,distributors in the down-stream, as well as government in the supporting sub-systems, in orderto deliver agricultural products to the customers. TH is the agricultural business aggregatorthat connects the whole agribusiness system. Secondly, based on the business performance,Covid-19 pandemic has affected agricultural business aggregators differently due to itsbusiness nature. It seems that vegetables, fruits and staple foods as the essential goods for aliving contributed to the higher business performance of agricultural business aggregators.